Stabat Mater: The Impossible Mourning in Teresa Ferenc’s Poetry - Szopa, Katarzyna (Porównania, 2023)
The article discusses the feminist politics of mourning in the poetry of Teresa Ferenc. The main assumption of the text is to highlight the subversive potential of the medieval motive of Stabat Mater. By referring to feminist anthropology, as well as the psychoanalyst theory of Julia Kristeva, I argue that behind the figure of mother’s grieving lies not only the poet’s opposition to war, but also an ethical imperative of solidarity with others, i.e. nameless victims of any kind injustice provided by patriarchal-capitalist policy.